Tricarboxylic acid cycle of glia in the in vivo human brain - Blüml, S.; Moreno-Torres, A.; Shic, F.; Nguy, C.-H.; Ross, B. D. (NMR in biomedicine, 2002)
In the brain, acetate is exclusively oxidized by glia. To determine the contribution of glial metabolism to the tricarboxylic acid cycle (TCA), 1‐13C‐acetate was infused in six studies in three normal adult subjects and one epileptic receiving valproic acid for seizure control. Ten grams of 99% 1‐13C labeled acetate were infused intravenously as a 3.3% w/v solution over 60 min, during which in vivo 13C MR spectra of the brain were acquired. As expected, 13C label rapidly enriched cerebral bicarbonate, glutamate and glutamine C5. The mean rate of acetate oxidation calculated from steady‐state 13C enrichment of bicarbonate in fasted normal subjects was 0.13 ± 0.03 µmol/g/min (n = 4), approximately 20% of the total cerebral TCA cycle rate. Copyright © 2002 John Wiley & Sons, Ltd.